The plastic scintillator activated with fluorinated 3-hydroxyflavone - Gurkalenko, Yu.A.; Eliseev, D.A.; Zhmurin, P.N.; Pereymak, V.N.; Svidlo, O.V. (Functional Materials, 2017)
A new radiation-hard plastic scintillator (PS), based on polystyrene and activated with fluorinated 3-hydroxyflavone, is presented. The new scintillator has the light output half-attenuation dose equal to 11 Mrad, which is much more than a similar PS, containing 3-hydroxyflavone. Also, the temporal characteristics of the PS are investigated. The scintillation flash rise time was 0.5 ns, what is much faster than the rise time of conventional PS, equal to about 0.9 ns. Such properties of the new PS are achieved by application of fluorinated 3-hydroxyflavone as an activator.